(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVES: This study evaluated by three-dimensional finite element analysis the tensions generated by different disocclusion patterns (canine guide and bilateral balanced occlusion) in an implant-supported mandibular complete denture. MATERIAL AND METHODS: A three-dimensional model of implant-supported mandibular complete denture was fabricated according to the Brånemark protocol. A 5-element 3.75 x 13-mm screw-shape dental implant system was modeled for this study. The implants were located in the inter-mental foramen region with 3-mm-high prosthetic components joined by a nickel-chromium framework with 12-mm bilateral cantilever covered by acrylic resin and 12 acrylic denture teeth. SolidWorks® software was used before and after processing the simulations. The mechanical properties of the components were inserted in the model and a 15 N load was established in fixed points, in each one of the simulations. Data were collected in the entire nickel-chromium framework. The results were displayed three-dimensionally as color graphic scales. RESULTS: The canine guide generated greater tensions in the region of the first implant, while the bilateral balanced occlusion generated great tensions in the entire metallic framework. The maximum tension found in the simulation of the bilateral balanced occlusion was 3.22 fold higher than the one found in the simulation of the disocclusion in canine guide. CONCLUSION: The pattern of disocclusion in canine guide is the ideal for implant-supported mandibular complete denture.